Penerapan Metode Design Thinking Pada Aplikasi Donasi Sedekah Jum’at Rutin Yayasan Aisyah Berbagi Berbasis Website - Karisma, Elana; Mansur, Mansur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Yayasan Aisyah Berbagi is a social foundation that runs the Sedekah Jum’at Rutin program, which aims to support orphans, the poor, and the underprivileged. However, several issues still exist, including ineffective information dissemination, manual processes for both donations and donation submissions, lack of transparency in donation pickups, and manual donation reporting. This research aims to apply the design thinking method in developing a web-based donation application for Yayasan Aisyah Berbagi’s Sedekah Jum’at Rutin program, with the goal of increasing donation process efficiency, expanding donor reach, and making it easier for the public to submit donations. The results show that implementing this method effectively addresses the existing problems within Yayasan Aisyah Berbagi. With the introduction of this web-based donation application, the donation process is expected to become more practical, transparent, and well-organized, allowing Yayasan Aisyah Berbagi to optimize its fundraising efforts more effectively.